Matrix infinite-dimensional analog of the Wiener theorem on local inversion of Fourier transforms - Degtyar', S. V.; Shurenkov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
A matrix infinite-dimensional analog of the Wiener theorem on local inversion of Fourier transforms is proved.